Primahin diphosphate against experimental theileriosis of cattle - M. R. Sakhimov (Российский паразитологический журнал)
The results of primahin diphosphate using against experimental theileriosis of cattle are given. Primahin diphosphate in a doses of 0,63 and 0,9 mg/kg renders 100 % efficiency against theileriosis of cattle